Touched by fire : a National Historical Society photographic portrait of the Civil War, in association with Civil War times - Davis, William C., 1946-; Frassanito, William A.; National Historical Society (New York : Black Dog & Leventhal, 1997)
Presents photographs of Civil War events with essays by noted historians
Originally published: Boston : Little, Brown, 1985. 2 v.
Includes index.
Keywords: United States -- History -- Civil War, 1861-1865 -- Pictorial works; United States -- History -- 1861-1865, Civil War -- Pictorial works